Impact of credit facilities and contemporary economic environment on the accessibility to credit of customers: Case study in Binh Duong, Vietnam - Nguyen Hong Thu; Le Kieu Oanh Dao; Do Thi Thanh Nhan (Contemporary Economics, 2022)
Recently, accessibility to credit has become a global issue and need to be examined frequently that needs the attention of regulators and researchers. Thus, this study examines the credit facilities (the price of credit and reliability of credit sources) on the accessibility of customer credit at commercial banks in Binh Duong Province, Vietnam, in the context of the COVID-19COVID-19 pandemic. The study also examines the moderating role of the contemporary economic environment among the nexus of the price of credit, reliability of credit sources and accessibility of the credit of customers at commercial banks in Binh Duong Province. The findings suggested that the price of credit has negative while reliability of credit sources have a positive impact on the accessibility of the credit of customer at commercial banks. The results also revealed that the contemporary economic environment significantly moderates among the nexus of the price of credit, reliability of credit sources and accessibility of the credit of customers at commercial banks.
Keywords: G41; G28; D31; 330; COVID-19 pandemic; accessibility to credit; contemporary economic environment price of credit; reliability of credit sources